Rationalization of Interactions in Precious Metal/Ceria Catalysts Using the d‐Band Center Model. Issue 30 (18th June 2013) - Acerbi, N.; Tsang, S. C. Edman; Jones, G.; Golunski, S.; Collier, P.
<x xml:space="preserve">Abstract</x> A correlation between ceria reducibility and the precious‐metal d‐band center is reported for ceria‐supported precious‐metal catalysts. The results could provide the missing link to fully explain the occurrence of strong metal–support interaction (SMSI) and hydrogen spillover in catalysts that consist of dispersed metals in contact with reducible metal oxides.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>